A community-led intervention to build neighbourhood identification predicts better wellbeing following prolonged COVID-19 lockdowns - Cruwys, Tegan; Fong, Polly; Evans, Olivia; Rathbone, Joanne A. (Frontiers in Psychology, 2022)
A growing body of research supports the importance of social cohesion for population wellbeing. However, the majority of this research has been correlational, and rarely have interventions been evaluated. We conducted a two-timepoint study investigating the role of Neighbour Day, a grass-roots, community-led intervention that seeks to build social cohesion across the population. Among a sample of 843, 125 were Neighbour Day participants while the remainder were not. We found that, compared to non-participants, Neighbour Day participants had significantly higher neighbourhood identification, experienced greater social cohesion, and had larger neighbourhood social networks. Between timepoints, the majority of the sample experienced prolonged lockdowns to prevent COVID-19 transmission, and so unsurprisingly, wellbeing declined and psychological distress increased. However, Neighbour Day participants were protected against these negative mental health effects of lockdown. These benefits of Neighbour Day participation were mediated via neighbourhood identification. Overall, the findings speak to the promise of large-scale interventions to build social identity, particularly due to their capacity to build resilience and protect people’s wellbeing during times of collective change or crisis.